2010
DOI: 10.1186/1479-5876-8-99
|View full text |Cite
|
Sign up to set email alerts
|

MMP-1 is a (pre-)invasive factor in Barrett-associated esophageal adenocarcinomas and is associated with positive lymph node status

Abstract: BackgroundEsophageal adenocarcinomas (EACs) arise due to gastroesophageal reflux, with Barrett's esophagus (BE) regarded as precancerous lesion. Matrix metalloproteinases (MMPs) might play a role during the multistep carcinogenetic process.MethodsExpression of MMP-1 and -13 was analyzed in esophageal cancer (n = 41 EAC with BE, n = 19 EAC without BE, and n = 10 esophageal squamous-cell carcinomas, ESCC), furthermore in BE without intraepithelial neoplasia (IN) (n = 18), and the cell line OE-33. MMP-1 was co-la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 49 publications
(50 reference statements)
3
28
0
2
Order By: Relevance
“…They are involved in the processes of inflammation and carcinogenesis, as many are produced by inflammatory and stromal cells, and so may have a role in inflammatory-driven cancers. In the oesophagus, MMP-1 has been found to be increased in BO and Barrett's-derived cancers and in OAC cell lines; it also correlates with lymph-node metastasis and poor prognosis [49][50][51]. Another study found that MMP-1, -3, -7 and -10 along with TIMP-1 were increased along the sequence from BO to OAC [19].…”
Section: Role Of the Extracellular Matrixmentioning
confidence: 88%
“…They are involved in the processes of inflammation and carcinogenesis, as many are produced by inflammatory and stromal cells, and so may have a role in inflammatory-driven cancers. In the oesophagus, MMP-1 has been found to be increased in BO and Barrett's-derived cancers and in OAC cell lines; it also correlates with lymph-node metastasis and poor prognosis [49][50][51]. Another study found that MMP-1, -3, -7 and -10 along with TIMP-1 were increased along the sequence from BO to OAC [19].…”
Section: Role Of the Extracellular Matrixmentioning
confidence: 88%
“…48 Hence, this MMP may be related to another mechanism than the PA-system, coming at onset of invasion. It has also been reported that a low host inflammatory response in the vicinity of the adenocarcinoma cells indicates a poor prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Esophageal adenocarcinoma is related to gastroesophageal reflux and Barrett's esophagus, which is regarded as a precancerous lesion. Expression of MMP-1 was found in 95% of cases of ACE with BE and in 100% of cases of ACE without BE, whereas no expression of MMP-13 was found in these specimens [52]. Moreover, increased MMP-1 expression was observed in tumor cells positive for Ki-67 (the marker of cells' proliferation) whereas high MMP-1-mRNA levels were associated with lymph node metastases [52].…”
Section: Other Mmpsmentioning
confidence: 97%